Bromocriptine treatment of acromegaly. Issue 5953 (8th February 1975) - Thorner, M O; Chait, A; Aitken, M; Benker, G; Bloom, S R; Mortimer, C H; Sanders, P; Mason, A S; Besser, G M
Abstract : The effects of oral bromocriptine in acromegaly have been studied. A dose of 5 mg six-hourly suppressed circulating growth hormone (GH) levels in nine out of 11 patients treated for seven to 11 weeks. This was associated with considerable clinical improvement in all patients, with abolition of excessive sweating, reduction in soft-tissue thichening, loosening of rings, decrease in shoe size, improvement in facial features, and loosening of dentures. Metabolic changes included improvement in glucose tolerance and reduction in hydroxyproline excretion. Unlike the actions of growth hormone release inhibiting hormone the suppression of GH was not accompanied by a reduction in insulin or glucagon secretion, though prolactin levels were suppressed. Side effects other than mild constipation were not seen when the full dose regimen was reached by slowly increasing the dose from 2-5 mg once daily. Bromocriptine holds promise as a safe and orally effective medical treatment to augment surgical or radiotherapeutic measures directed at the pituitary tumour. Its efficacy during longterm administration remains to be established.